2019
DOI: 10.3389/fpsyt.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism but Not Criminality Is Associated With Aggression in Women: A Study Among Female Prisoners and Women Without a Criminal Record

Abstract: Aggression has drawn research attention during the past decades. It remains unclear how self-esteem, self-perception, narcissism and certain socio-demographic factors impact the course of aggression. Female aggression is considered to differ in its origins and is understudied. Only few studies have attempted to examine the aforementioned variables among females, while none of them included a comparison between delinquent and non-delinquent individuals. The present study examines the effect of self-esteem, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
2
6
0
1
Order By: Relevance
“…The results from Step 2 of the hierarchical Cox regression (see Table 4), and before entering psychopathy to the model, showed that passive–aggressive PD and narcissistic PD are significant predictors of criminal behavior in schizophrenia. This is consistent with findings suggesting that passive–aggressive PD (Berman, Fallon, & Coccaro, 1998) and narcissistic PD (Kalemi et al, 2019) are significant predictors of aggressive behavior. However, with the inclusion of all four facets of the PCL-R, results showed that in addition to passive–aggressive PD and narcissistic PD, global functioning, and the Lifestyle and Antisocial facets of the PCL-R considerably contributed to the prediction of criminal behavior.…”
Section: Discussionsupporting
confidence: 91%
“…The results from Step 2 of the hierarchical Cox regression (see Table 4), and before entering psychopathy to the model, showed that passive–aggressive PD and narcissistic PD are significant predictors of criminal behavior in schizophrenia. This is consistent with findings suggesting that passive–aggressive PD (Berman, Fallon, & Coccaro, 1998) and narcissistic PD (Kalemi et al, 2019) are significant predictors of aggressive behavior. However, with the inclusion of all four facets of the PCL-R, results showed that in addition to passive–aggressive PD and narcissistic PD, global functioning, and the Lifestyle and Antisocial facets of the PCL-R considerably contributed to the prediction of criminal behavior.…”
Section: Discussionsupporting
confidence: 91%
“…This was mainly due to lower physical aggressiveness (Figure 2) in the absence of a difference in verbal ( Figure 3) and indirect (Figure 4) aggressiveness. According to some researchers, women mainly use indirect, relational aggression [7]. According our results, women didn't differ from men by indirect aggressiveness.…”
Section: Materials and Methods The Study Involved 119supporting
confidence: 43%
“…The investigations of the mechanisms of aggressiveness development in women are practically absent. Female aggression is considered to differ from male and findings from male samples can not apply to females [7]. Few studies mainly concerned manifestations of aggressiveness in women at various pathological conditions [8] or in women prisoners [7].…”
Section: Interrelationship Differences Between Personality Traits In mentioning
confidence: 99%
“…Over the decades, several studies have endeavoured to refine the construct of narcissism (Krizan & Herlache, 2017;Russ et al, 2008). Such studies have sought for viable applications of narcissism in social (Huang, Krasikova, & Harms, 2019), criminal (Kalemi et al, 2019;Stone, 2007), and clinical (Kacel et al, 2017) domains.…”
Section: Public Interest Statementmentioning
confidence: 99%